Nexus Capacity Scorecard (NCS) - Education and Research: guidance note and tool - Khalid, Sidra; Elias, M. (International Water Management Institute, 2024)
The Water–Energy–Food–Ecosystem (WEFE) nexus approach represents a holistic and interconnected perspective for addressing the complex interdependencies among water, energy, food, and ecosystems. This integrated perspective highlights the importance of managing WEFE resources collaboratively to achieve social, economic, and environmental sustainability. The ‘Nexus Capacity Scorecard (NCS) – Education and Research’ is intended to gauge capacities to adopt a WEFE nexus approach within and/or across academic institutions conducting research in or teaching courses related to the water, energy, food/agriculture, and environmental sectors (henceforth referred to as ‘WEFE academic institutions’). The purpose is to identify opportunities, possible gaps, and inform the planning of tailored WEFE nexus courses and research, and/or their monitoring over time. This version of the scorecard is part of a toolkit that includes the original Nexus Capacity Scorecard (NCS), which supports the self-assessment of nexus capacities within and/or across WEFE institutions or organizations in government, the private sector, or civil society.